Moral Religiusitas Siswa Sekolah Dasar Dilihat dari Perspektif Filsafat Idealisme - Auliyana Rahmah Harahap; Yakobus Ndona; Ibrahim Gultom (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to understand the morality of elementary school students. This research employs a literature review method. The data collection technique involves gathering previous studies and several journals to address the morality of elementary school students from the perspective of idealism philosophy. The data in this research is obtained from library research, which is used to explore a deeper understanding of the basic concepts of philosophy of education and their relevance in the development of the education system. The data from previous studies that has been collected is then compiled, analyzed, and concluded to derive conclusions about the religious morality of elementary school students from the perspective of idealism philosophy. The conclusion of this research is that morality and religiosity can be linked because both emphasize that intangible aspects, such as moral values or spiritual beliefs, are more important than physical or material aspects.